A Study on the Analysis of the Ground Compaction Effect According to the Roller Operation Method through CMV Analysis Using IC Rollers - Jinyoung Kim; Sung-Yeol Lee; Jin-woo Cho (Advances in Civil Engineering)
In road construction, the compaction process using vibratory rollers is essential to increase the ground stiffness in earthworks. There need to be clear standards regarding the operation of compaction rollers during compaction work. Various simple quality inspection techniques have been developed to check the stiffness of the ground, but plate load test and field density test are the most commonly used test methods to evaluate the degree of compaction during road construction. However, both inspection methods could be more efficient, as they cannot be performed in all sections due to time and cost. Additionally, in compaction work today, the worker will individually judge the number of compactions, thickness, speed, vibration etc. based on his or her own experience. This means that the quality of compaction varies depending on the worker. In this study, quality inspection results for all sections were obtained using an intelligent quality control system that employs an IC roller, a technology that is now commercially available. The effect of the operating conditions of the vibrating roller (roller compaction direction, compaction roller speed, and compaction roller vibration method) on the compaction quality was analyzed using the intelligent quality control value. Through our highway construction site tests, it was found that the speed of the compaction roller and the vibration method of the compaction roller affected the degree of compaction, but the direction of compaction did not. Therefore, if the compaction work is performed by adjusting the driving speed and vibration method of the vibrating roller according to the ground conditions, repetitive compaction work can be reduced, thereby reducing construction costs and lowering work time, which will achieve an improved work efficiency.